Identifying etiological pattern for postpartum complications - D. F. Kurbanova; S. G. Sultanova; F. R. Hajiyevа (IRBIS LLC, 2022)
Introduction. Postpartum complications hold one of the leading places in the pattern of gynecological diseases.Aim: to study the clinical and laboratory features of developing postpartum inflammatory complications.Materials and Methods. There were examined 150 puerperas at the Scientific Research Institute of Obstetrics and Gynecology (Baku, Azerbaijan) in the years from 2019 to 2021, who were subdivided into 2 groups: the main group - puerperas with developed postpartum complications (n = 100), aged 29.9 ± 0.64 years and the control group - puerperas with a physiological course of postpartum period (n = 50), aged 30.3 ± 0.86 years (p = 0.679). We studied the general and obstetric-gynecological anamnesis. The following parameters of the peripheral blood samples were analyzed: total leukocyte count, absolute and relative lymphocyte level, erythrocyte and platelet counts, the hemoglobin concentration, erythrocyte sedimentation rate, and quantity of serum interleukin-6 (IL-6).Results. It was found that puerperas of the main vs. control group had increased level of serum pro-inflammatory cytokine IL-6 (24.26 ± 0.48 pg/ml vs. 10.36 ± 0.62 pg/ml; p = 0.001) considered as an additional risk factor for developing postpartum complications. Regarding cellular immune parameters, they were shown to have decreased CD4+/CD8+ ratio due to blood elevated CD8+ lymphocyte count and decreased level of CD4+ T-cells. The development of postpartum inflammatory complications in the main group was associated with menstrual disorders in 81.0 ± 3.92 % of cases, first births - in 60.0 ± 4.90 %, threatened miscarriage - in 19.0 ± 3.92 % and gestational toxicosis - in 52.0 ± 5.00 % of the total cases. Some risk factors were associated with diseases of the genitourinary system (main vs. control groups: chronic pyelonephritis 24.0 ± 4.27 % and 10.0 ± 4.24 %, respectively; p = 0.048) and respiratory organs, most often represented by chronic tonsillitis and sinusitis (main vs. control groups: 20.0 ± 4.00 % vs. 4.0 ± 2.77 %, respectively; p = 0.007).Conclusion. The course of the postpartum period in primiparas as well as women with burdened history of obstetric-gynecological and extragenital pathology is characterized by a high proportion of inflammatory complications. Biochemical studies assessing peripheral blood T-lymphocyte count and serum level of the pro-inflammatory cytokine IL-6 can be used as an additional diagnostic method to identify and assess modality and severity of early puerperal complications.